Spiral like integral operators - Shyam K. Bajpai (International Journal of Mathematics and Mathematical Sciences)
In this paper we investigate the Robertson-Libera integral operators for the class of spiral like univalent and analytic functions. We find that special types of transformations preserve the class property. Our results generalize or sharpen the results recently obtained by Miller et al [7] and by Causey and White [3].